Phenolic content and antioxidant activity of mushroom extracts from Bosnian market - Alispahić, Amra; Šapčanin, Aida; Salihović, Mirsada; Ramić, Emina; Dedić, Amila; Pazalja, Mirha (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2015)
Mushrooms are well balanced food that provides definite nutrition and health benefits for humans. Mushrooms are known to produce different kinds of bioactive compounds, generally linked with mycelial cell wall, that help in enhancing the capacityof immune system to fight against carcinogens. To consider the importance of polyphenolic compounds and its presence in many varieties of mushrooms, the total antioxidant activity of dry boletus mushroom, white and brown champignon, oyster mushroom and shiitake from bosnian markets was determined. Total phenolic content was estimated as Galic acid equivalents /g spectrophotometrically according to the Folin-Ciocalteus method. Total anthocyanine content was analysed by pH differential spectrophotometric method at 525 and 700 nm. The radical scavenging activity (RSA) of mushroom extracts was determined by 1,1-diphenyl-2-picrylhydrazyl(DPPH) assay. The analysis revealed that the total phenolic contents ranged from 4.94 mg GAEg-1 in oyster mushroom to 35.56 mg GAEg-1 in dry boletus mushroom. DPPH scavenging activity was the highest for brown champignon with value of 88.33 % and the lowest one was for oyster mushrooms with value of 43.88 %. The mushrooms examined in the present study could represent easily accessible sources of natural antioxidants.